Implementasi Pelayanan Jemput Bola Adminduk di Balai RW dalam Meningkatkan Kualitas Pelayanan Publik di Kelurahan Genteng Kota Surabaya - Anjainah, Najwa Tsaniya; Hardjati, Susi (VISA: Journal of Vision and Ideas, 2025)
This research aims to analyze the implementation of population administration pick-up and drop-off services in supporting public services in Genteng sub-district. The main focus of this research is on the process of implementing strategies and efforts to overcome the obstacles faced during the implementation process of the population administration pick-up and drop-off program in Genteng sub-district in realizing good governance in Surabaya city government. This research uses empirical research with descriptive research characteristics and qualitative research methods. The data sources used in this research consist of primary data and secondary data. The data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of digital population identity has gone well, especially based on analysis using implementation theory according to George C. Edward III. The indicators used to measure the success of this strategy include resources, disposition and bureaucratic structure, however the consistency of communication indicators is still not running optimally. The results of this research conclude that the population administration pick-up service utilizing digital technology runs smoothly and the implementation process improves and supports public services in the community of Genteng sub-district, Surabaya city. We can see obstacles that show that there were problems encountered during the implementation process, namely limited facilities and low community participation due to lack of socialization and public awareness of the importance of owning population documents is still low.